A FRENCH PARADOX?: Toward an Explanation of Inconsistencies between Framing and Policies. Issue 2 (1st July 2019) - Bergeron, Henri; Castel, Patrick; Saguy, Abigail C.
Abstract : The French news media has framed "obesity" largely as a product of corporate greed and social inequality. Yet, France has—like other nations including the United States—adopted policies that focus on changing individual-level behavior. This article identifies several factors—including food industry lobbying, the Ministry of Agriculture's rivalry with the Ministry of Health and alliance with the food industry, and competition with other policy goals—that favored the development of individual-level policy approaches to obesity in France at the expense of social-structural ones. This case points to the need to more systematically document inconsistencies and consistencies between social problem framing and policies. It also shows that national culture is multivalent and internally contradictory, fueling political and social struggles over which version of national culture will prevail at any given moment.